2022
DOI: 10.1038/s41396-022-01284-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic fungus uses volatiles to entice male flies into fatal matings with infected female cadavers

Abstract: To ensure dispersal, many parasites and pathogens behaviourally manipulate infected hosts. Other pathogens and certain insect-pollinated flowers use sexual mimicry and release deceptive mating signals. However, it is unusual for pathogens to rely on both behavioural host manipulation and sexual mimicry. Here, we show that the host-specific and behaviourally manipulating pathogenic fungus, Entomophthora muscae, generates a chemical blend of volatile sesquiterpenes and alters the level of natural host cuticular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Another striking E. muscae phenomenon has been observed in house flies infected with E. muscae s.s.: healthy males tend to be attracted to and attempt to mate with E. muscae-infected female cadavers (Mullens et al, 1987;Møller, 1993;Zurek et al, 2002;Hansen and De Fine Licht, 2019). Very recent work has provided additional evidence of this phenomenon and found that volatile compounds (including sesquiterpenes and putative pheromone mimics) that have a likely fungal origin are involved in mediating this fatal attraction (Naundrup et al, 2022).…”
Section: Extended Phenotypes Of E Muscaementioning
confidence: 98%
See 4 more Smart Citations
“…Another striking E. muscae phenomenon has been observed in house flies infected with E. muscae s.s.: healthy males tend to be attracted to and attempt to mate with E. muscae-infected female cadavers (Mullens et al, 1987;Møller, 1993;Zurek et al, 2002;Hansen and De Fine Licht, 2019). Very recent work has provided additional evidence of this phenomenon and found that volatile compounds (including sesquiterpenes and putative pheromone mimics) that have a likely fungal origin are involved in mediating this fatal attraction (Naundrup et al, 2022).…”
Section: Extended Phenotypes Of E Muscaementioning
confidence: 98%
“…The building of pressure by the cytoplasm that accumulates inside conidiophores puts pressure on the cell wall linking the conidium and conidiophore (called a septum), leading to the conidium being forcefully ejected via a water cannon mechanism (de Ruiter et al, 2019). For 20-24 hours in E. muscae-infected house fly cadavers, thousands of conidia are shot out of the fungal mass exposed from the abdomen of the old host, forming a halo of spores surrounding the cadaver (Mullens, 1985;Carruthers and Haynes, 1986;Elya et al, 2018;Naundrup et al, 2022) (Fig. 3).…”
Section: Infection Of New Hostsmentioning
confidence: 99%
See 3 more Smart Citations